2004
DOI: 10.1002/bit.10834
|View full text |Cite
|
Sign up to set email alerts
|

On‐line monitoring of human prostate cancer cells in a perfusion rotating wall vessel by near‐infrared spectroscopy

Abstract: PC-3 human prostate cancer cells have been cultivated in a rotating wall vessel in which glucose, lactate, and glutamine profiles were monitored noninvasively and in real time by near-infrared (NIR) spectroscopy. The calibration models were based on off-line spectra from tissue culture experiments described previously (Rhiel et al., Biotechnol Bioeng 77:73-82). Monitoring performance was improved by Fourier filtering of the spectra and initial off-set adjustment. The resulting standard errors of predictions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…On the contrary, the LWR method was shown to be more robust during this phase since culture spectra were always incorporated into the local PLSR space in order to perform a regression. [47][48][49] In this context, LWR has been proven as a promising method to perform in situ monitoring since it allowed calibration in a wide concentration frame, and also considered the nature of the culture medium. They could also be attributed to the lack of precision or to the presence of noise since even the LWR method showed prediction errors, although weaker, after 120 hr.…”
Section: Real Time Monitoring Of Animal Cell Culture Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, the LWR method was shown to be more robust during this phase since culture spectra were always incorporated into the local PLSR space in order to perform a regression. [47][48][49] In this context, LWR has been proven as a promising method to perform in situ monitoring since it allowed calibration in a wide concentration frame, and also considered the nature of the culture medium. They could also be attributed to the lack of precision or to the presence of noise since even the LWR method showed prediction errors, although weaker, after 120 hr.…”
Section: Real Time Monitoring Of Animal Cell Culture Processesmentioning
confidence: 99%
“…18,22,46 Some other authors have overcome nonlinearity behavior of NIR monitoring models by using at-line analyses of clarified culture medium, as already described. [47][48][49] In this context, LWR has been proven as a promising method to perform in situ monitoring since it allowed calibration in a wide concentration frame, and also considered the nature of the culture medium.…”
Section: Real Time Monitoring Of Animal Cell Culture Processesmentioning
confidence: 99%
“…Biological compounds can be coupled to the optode for the detection of targets, like glucose and hydrogen peroxide [16]. Near-infrared spectroscopy can quantify the concentration of certain organic species by the analysis of the adsorption bands in the spectrum [17]. Fluorescence sensors are based on the response of particular molecules which emit light after an excitation at particular wavelength.…”
Section: Transduction Mechanismmentioning
confidence: 99%
“…The studies of spectral differences between human cancer and normal tissues have been reported for breast [5], cervix [6], lung [7], colorectal [4], prostate [8,9], and other tissues. These studies were mostly based on the assignment of position and intensity of peaks.…”
Section: Introductionmentioning
confidence: 99%